A new iterative method for solving multiobjective linear programming problem - Matejas, Josip; Peric, Tunjo (Applied mathematics and computation, 2014)
In the paper we present a new iterative method for solving multiobjective linear programming problems with an arbitrary number of decision makers. The method is based on the principles of game theory. Each step of the method yields a unique solution which respects the aspirations of decision makers within the frame of given possibilities. Each decision maker is assigned an objective indicator which shows the reality of his aspiration and which may be used to define the strategy for the next step. The method can be easily extended to general (nonlinear) multiobjective programming problems but the numerical application would require further research on computational methods.